Analyzing the theoretical trajectory of “staleness” and its relevance to modern sports psychiatry <subtitle>A word of wisdom</subtitle> - Jill Colangelo; Alexander Smith; Anna Buadze; Michael Liebrenz (Sports Psychiatry)
Abstract: Introduction: Despite recent advancements in sports medicine and sports psychiatry, a lack of clarity remains in understanding the pathogenesis and etiology of Overtraining Syndrome (OTS). Early research on endurance athletes in high volume/intensity cycles of training described a condition of “staleness”, which could be detected using psychometric assessments on mood. Associated with both physical and psychological symptoms, “staleness” was found to be dose responsive and tended to abate with a reduction in training. Subsequent study of OTS has not revealed reliable or reproducible measurements for ascertaining or treating the condition. Methods: We reviewed historical literature discussing “staleness”, summarizing its theoretical trajectory in academic domains, and comparing this with more recent work that emphasizes the physiological parameters of OTS. We also consider the sociocultural context surrounding these terminological shifts. Results: Though the term “staleness” has fallen out of favor, past work into this topic may have relevance in attempts to define, diagnose, and treat OTS. Further, sports psychiatry may be in a unique position to revisit the literature and emphasize the utility of psychometric assessment in screening, as well as underlining the importance of maintaining mental health among high performing athletes. Conclusion: Research and psychometric assessments designed to discuss “staleness” still remain relevant, particularly in sports psychiatry, and may deserve to be revisited as well as expanded.